The effects of green tea supplementation on cardiovascular risk factors: A systematic review and meta-analysis - Zamani, Mohammad; Kelishadi, Mahnaz Rezaei; Ashtary-Larky, Damoon; Amirani, Niusha; Goudarzi, Kian; Torki, Iman Attackpour; Bagheri, Reza; Ghanavati, Matin; Asbaghi, Omid (Frontiers in Nutrition, 2023)
Purpose: A bulk of observational studies have revealed the protective role of green tea supplementation in cardiovascular diseases. The current systematic review and meta-analysis study aimed to establish the effects of green tea supplementation on cardiovascular risk factors including lipid profile, blood pressure, glycemic control markers and CRP. Methods: A systematic literature search of randomized clinical trials (RCTs) that investigated the effects of green tea supplementation and cardiovascular risk factors was undertaken in online databases including PubMed/Medline, Scopus, Web of Science, and Embase using a combination of green tea and cardiovascular risk factors search terms. Meta-analyses were carried out using a random-effects model. The I2 index was used to assess the heterogeneity of RCTs. Results: Among the initial 11286 studies that were identified from electronic databases search, 55 eligible RCTs with 63 effect sizes were eligible. Results from the random effects meta-analysis showed that GTE supplementation significantly reduced TC (WMD= -7.62; 95% CI: -10.51, -4.73; P=<0.001), LDL-C (WMD= -5.80; 95% CI: -8.30, -3.30; P=<0.001), FBS (WMD= -1.67; 95% CI: -2.58, -0.75; P=<0.001), HbA1c (WMD= -0.15; 95% CI: -0.26, -0.04; P=0.008), DBP (WMD= -0.87; 95% CI: -1.45, -0.29; P=0.003), while increasing HDL-C (WMD=1.85; 95% CI: 0.87, 2.84; P=0.010). Subgroup analyses based on the duration of supplementation (≥12 vs. <12 weeks), dose of green tea extract (GTE) (≥1000 vs. <1000 mg/d), sex (male, female, and both), baseline serum levels of lipid profile, and glycemic control factors demonstrated different results for some risk factors. Conclusion: The current study suggests improvements in the lipid and glycemic profiles following green tea supplementation. These findings support previous evidence showing the health benefits of green tea supplementation on cardiometabolic risk factors.